An investigation into the usage of ingested traditional chinese medicine among 30- to 80-year-old type 2 diabetic patients in Metro Manila - Coo, Cherise V.; Dy, Laila Denise M.; Pe, Jarren Cynric C.; Tengco, Lorena W. (University of the Philippines Diliman, 2025)
Type 2 diabetes mellitus is one of the most common ailments in the Philippines. Innovations in the healthcare and medical industries have been ongoing, with Western or conventional medicine leading the way in treatment prescriptions. Alternative and traditional medicinal practices, on the other hand, have existed for centuries. With the Philippines having a significant population of Chinese descent, it is evident that traditional Chinese medicine has had a profound impact on society; nonetheless, the literature on this topic is scarce. This study aims to determine the underlying factors that drive patients or consumers, specifically those with Type 2 diabetes mellitus, to choose traditional Chinese medicine and how these factors affect their choices regarding the consumption or use of conventional medicine or treatment. The study employed a qualitative approach, conducting face-to-face interviews with 10 participants from Metro Manila recruited using snowball sampling. Interview data were thematically analyzed based on the levels in the socio-ecological model to identify influencing factors. Findings revealed that intrapersonal factors, including cultural identity, perception, experiences, knowledge, and self-belief, had an impact on the use of traditional Chinese medicine, followed by interpersonal factors such as recommendations and support from family and peers, with institutional, community, and policy-level influences being minimal but still present. The resulting framework offers insight into patient decision-making and may inform more personalized approaches to diabetic nutrition counseling.
In partial fulfillment for the Degree of Bachelor of Science in Community Nutrition
Thesis
Keywords: Diabetes -- Treatment; Type 2 diabetes; Medicine, Chinese traditional -- Philippines; Diabetes -- Alternative treatment; Type 2 Diabetes mellitus (T2DM).; Traditional Chinese medicine (TCM).; Socio-ecological model (SEM).